The Role of Palanta Baselo Nagari Sungai Duo in Resolving Criminal Acts Through Restorative Justice in Multi-Ethnic Communities - Fitriati; Iyah Faniyah; Nurhadiansyah (Pandecta Research Law Journal, 2025)
Legal issues in a multiethnic society lie in the implementation of Article 2 of the Regulation of the Chief of Police Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice. One form of restorative justice is Palanta Baselo Nagari Sungai Duo which is used to resolve criminal cases in a multiethnic society in the jurisdiction of the Sitiung Police, Dharmasraya Police. This study aims to analyze the challenges faced by Palanta Baselo in handling criminal cases based on restorative justice. This research is empirical legal research with analytical descriptive specifications. The findings of the study conclude that the resolution of criminal cases through Palanta Baselo Nagari Sungai Duo in a multiethnic society in the jurisdiction of the Sitiung Police, Dharmasraya Police has been implemented. However, in practice, there is still a lack of facilities and infrastructure to support mediation. In addition, traditional figures who act as mediators also lack the skills to reconcile the disputing parties. Although the penghulu (traditional figure) is a respected and revered figure, they have not been equipped with the knowledge and skills to carry out mediation efforts effectively.